Pain Management with Ganglion Impar Block in Adenocarcinoma Recti - Yogo, Wi; Laksono, Ristiawan Muji; Asmoro, Aswoco Andyk; Isngadi, Isngadi; Laksono, Buyung Hartiyo; Jaya, Wiwi (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2024)
Background:Colorectal cancer is a type of malignant neoplasm that is often found with the third highest mortality rate in the world after breast cancer and lung cancer. Adenocarcinoma is the most common type of colorectal cancer which cause pain to the patient. The pain from this disease was described as chronic pain. Chronic pain can result from ongoing nerve inflammation and central sensitization. Inflammation begins with a mechanical injury which then turns into chronic inflammation. This situation changes the responsiveness of neurons to pain in the sympathetic ganglion. Sympathetic ganglia block is more effective in controlling visceral pain. This impar ganglion is the only sympathetic nervous system ganglion that is not attached to the sacrococcygeal. In this case report, the transsacrococcygeal joint approach was used to locate the ganglion accurately by injecting contrast and viewing the vertical dispersion called inverted commas along the ganglion laterally.Case Illustration: A 60-year-old female patient was admitted with complaints of pain around the anus. The patient has been diagnosed with Adenocarcinoma recti two years ago. Pain is felt like being stabbed and persists in the anal area. Pain intensity increases on sitting and defecation. The patient has undergone chemotherapy 12 times and is taking pain relievers that have been prescribed regularly. The patient's Numeric Rating Scale (NRS) score is 6-7, which is categorized as severe pain. This patient underwent ganglion impar block using the trans sacrococcygeal joint approach with the help of fluoroscopy to relieve the severe pain.Conclusion: Ganglion Impar Block (GIB) can be performed with significant results in reducing opioid use and reducing pain in patients with Adenocarcinoma recti. The technique of administering neurolysis agents with the help of fluoroscopy can be an option because it is very effective and simple